2018
DOI: 10.14202/vetworld.2018.1433-1439
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of whole grain flaxseeds (Linum usitatissimum) along with high cholesterol diet and its effect on hyperlipidemia and initiated atherosclerosis in Wistar albino male rats

Abstract: Background and Aim:Flaxseeds are known to have varying antihypercholesterolemic and antiatherogenic activity due to its lignan secoisolariciresinol diglucoside, alpha-linolenic acid, and omega-3 fatty acids. The beneficial effect of whole grain dietary flaxseed was evaluated experimentally in high cholesterol diet (HCD)-fed Wistar albino rats.Materials and Methods:Male Wistar albino rats (200 g) were divided into four groups of 12 rats each. Group I rats kept as control and given basal rat chew diet, Group II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…Hypercholesterolemia may be caused by an increased uptake of exogenous cholesterol and increased esterification of free fatty acids. HMGCR is the regulator for cholesterol synthesis; however, similar to previous studies, we observed an upregulation in the rate of expression of this particular gene upon administration of HFD in rats ( Jiang et al, 2018;Naik et al, 2018). Hyper-triacylglyceridemia may be due to inhibition of 7a-hydroxylase activity (Beigneux et al, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…Hypercholesterolemia may be caused by an increased uptake of exogenous cholesterol and increased esterification of free fatty acids. HMGCR is the regulator for cholesterol synthesis; however, similar to previous studies, we observed an upregulation in the rate of expression of this particular gene upon administration of HFD in rats ( Jiang et al, 2018;Naik et al, 2018). Hyper-triacylglyceridemia may be due to inhibition of 7a-hydroxylase activity (Beigneux et al, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…The secoisolariciresinol diglucoside (SDG), a plant lignan isolated from flaxseed, exerts a cytoprotective effect. Studies have confirmed that SDG suppresses dextran sulfate sodium salt-induced colitis [11], serves as an anti-inflammatory and barrier-protective agent in neuroinflammation [12], and exerts antihypercholesterolemic [13] and also angiogenesis and cardioprotection against ischemia-reperfusion injury [14]. In addition, SDG are effective in lowering blood pressure in individuals with hypertension and metabolic syndrome [15] and exert prevention and treatment of arrhythmias and ventricular remodeling postmyocardial infarction [16].…”
Section: Introductionmentioning
confidence: 91%
“…The sixth group (CA2: combined alternative 2) received HFD with no FO for the first 14 days, both n-3 PUFAs and the HFD from days 15-28; during the last 2 weeks of the experiment (days [29][30][31][32][33][34][35][36][37][38][39][40][41][42], the animals in this group received the SD and 25 mg/kg/day n-3 PUFAs (Table 1).…”
Section: Experimental Design and Diet Administrationmentioning
confidence: 99%
“…P < 0.05 was considered significant. 42, indicating that n-3 PUFAs offer significant protection against excessive weight gain (WG) under HFD conditions (P < 0.001, HFD vs. HFD + n3 groups). In the CA1 group, the BW increase was higher than that observed in the n3 group (P < 0.01) and lower than that observed in the HFD group (P < 0.001); for the CA2 group, it was higher than that in the n3 group (P < 0.01) and lower than that in the HFD group (P < 0.01).…”
Section: Statistical Data Analysismentioning
confidence: 99%